On the theory of problems and their solution spaces - Agama, Theophilus (My University, 2022)
We introduce and develop the logic of existence of solution to problems. We use this theory to answer the question of Florentin Smarandache in logic. We answer this question in the negative.
Keywords: problem space; problem